"Listening Learning Self‐Efficacy and Self‐Regulation Strategies in the EFL Blended Context" - Lv, Chunlan (Journal of Theory and Practice of Social Science, 2024)
The study investigated the EFL learners’ listening learning self‐efficacy and self‐ regulated behavior in the blended context. 316 English major students were invited to offer their responses to the self‐efficacy and self‐regulated strategies in their blended listening learning process. Results showed that the students’ self‐efficacy and self‐ regulation strategies were at moderate levels. In addition, the result showed that male students had higher level of self‐efficacy and self‐regulation strategies in their listening learning; there was no significance differences between self‐efficacy and self‐regulation strategies when grouped by grade level. Listening self‐efficacy and self‐regulation strategies was positively related. Some suggestions were proposed to further improve students’ listening learning efficiency and teaching quality in the blended learning situation.